DIAGNOSTIC UTILITY OF FISH FOR MDM2 IN ADIPOCYTIC NEOPLASMS - Sarwar, Saud; Mushtaq, Sajid; Hassan, Usman; Maqbool, Hina; Qazi, Romena (Journal of Ayub Medical College Abbottabad, 2021)
Background: The 2013 World Health Organization (WHO) classification of soft tissue and bone tumours recognizes benign entities such as lipoma and four major liposarcoma subtypes: atypical lipomatous tumour/well differentiated liposarcomas (ALT/WDL), dedifferentiated liposarcomas (DDL), myxoid liposarcoma and pleomorphic liposarcoma. This classification of atypical and malignant adipocytic tumours has evolved significantly over the past few decades owing to contributions from cytogenetics, molecular genetics and Immunohistochemical correlates. Most ALT/WDLs can be diagnosed on histology, however, some of the biopsies may be underdiagnosed due to focal atypia or limited nature of tissue for the biopsy. Fluorescence in situ hybridization (FISH) for MDM2 (located at 12q14-15) gene amplification has emerged as gold standard for diagnosis in cases with limiting histological factors. Methods: We studied MDM2 amplification by FISH in 55 such problematic adipocytic tumours with overlapping morphological features and a retrospective analysis was made against their corresponding histological features. Results: MDM2 amplification correctly identified 11 of 17 ALT/WDLs (64.71% concordance) and 8 of 10 Lipomas (80% concordance). We were able to differentiate liposarcomas from other high grade sarcomatous lesions and sub-classified these lesions into pleomorphic and dedifferentiated types. Conclusion: FISH for MDM2 amplification should be used as a gold standard in adjunction with morphology and immunohistochemistry for problematic adipocytic neoplasms